Elaboración y aplicación de un manual guía para la organización y archivo de la documentación del departamento de planificación académica de la unidad de ciencias administrativas y humanísticas de la universidad técnica de cotopaxi - Morales Paredes, Verónica Alexandra (2015)
Cotopaxi Technical University, located in San Felipe sector, Eloy Alfaro Parish, Simon Rodriguez Avenue; is a prestigious Institution of Higher Education, which fights for the community welfare, especially for people who have low economic resources, constantly seeking for quality in education and excellence; by trying to fulfill both internal and external demands. The Organization and File Manual has been carried out with the purpose to create a guide for the Administrative staff from the Academic Planning Department of the Administrative Sciences and Humanities academic Unit that has direct relation with the documentation file with the aim of improving document management and in this way allow faster and effective access to the documentation….